Effects of customer perceptions in multichannel retail banking. Issue 5 (1st July 2019) - Bravo, Rafael; Martínez, Eva; Pina, José Miguel
Abstract : Purpose: This paper focuses on the multichannel strategy in the banking sector and its effects on customer engagement. Specifically, the purpose of this paper is to propose a model in which customers' perceptions of offline and online channels are related to brand trust and brand commitment, which ultimately lead to customer engagement. Design/methodology/approach: An empirical study was carried out on a sample of 306 individuals and data were analysed through partial least squares. Findings: The results show that offline experience is more important than online experience in terms of impact on trust and commitment, which are closely linked to customer engagement. Online experience does not have a significant direct influence on brand commitment and its effect on brand trust is moderated by the customer's familiarity with the channel. Originality/value: These findings contribute to the advance in the current knowledge of the joint role of online and offline channels with the aim of strengthening customer relationships. From a managerial viewpoint, customer perceptions formed by their experiences in bank branches are more important than customer perceptions of the website's performance in the explanation of trust and commitment.